Engaging African American Pastors in COVID-19 Research During a Pandemic: Lessons Learned. (December 2021) - Hayes, Traci; Baskin, LaWanda; Funchess, Tanya; Lowe, Samaria; Mayfield-Johnson, Susan
African American pastors are recognized as trusted information sources for their communities. The pastors willing to address health-related concerns such as preventing the spread of the coronavirus are invaluable for leading their congregation through relevant health programs. Underlining the importance of religion, spirituality, and faith-based leaders in addressing and furthering health promotion research, the article discusses lessons learned during the study implementation and the recommendations for engaging minority pastors in research during a global health pandemic.